Rosacea-specific quality of life questionnaire: translation, cultural adaptation and validation for Brazilian Portuguese - Flávia Cisi Tannus; Fabíola Rosa Picosse; Juliana Marques Soares; Edileia Bagatin (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Brazil does not have a rosacea-specific quality of life questionnaire. Objectives: translation into Brazilian Portuguese, development of cultural adaptation, and validation of the RosaQoL disease-specific questionnaire for rosacea of any subtype. Methods: the recommended procedures for translation, cultural adaptation, and validation of an instrument were followed, and three interviews were conducted: baseline; seven to fourteen days after baseline; and at four to six months. The questionnaire was analyzed (with 95% confidence interval) for reliability by internal consistency (Cronbach's alpha); testretest reproducibility (intraclass correlation coefficient); responsiveness and validity. Results: terms of the original questionnaire were replaced to guarantee cultural and semantic equivalence. Validity was demonstrated by expressive correlations between the RosaQoL domains and by significance in the Jonckheere-Terpstra test (p≤0.05) between the scores of the RosaQoL domains and the participants' self-perception in relation to the disease. Reliability was acceptable; alpha coefficient ranged from 0.923 to 0.916 in the first and second applications of the RosaQoL, respectively, and the Intraclass Correlation Coefficient (ICC) ranged from 0.671 to 0.863 in the seven- to fourteen-day period. Responsiveness, measured by grouping participants into three categories based on self-perception of rosacea (better, worse or unchanged), was found for the "better" response group (p≤0.05). Study limitations: small sample; limited variety of screening sources. Conclusions: RosaQoL-BR (Brazil) was demonstrated as a reliable, valid and responsive questionnaire, with limitations, for individuals with any subtype of rosacea.